Tales from a not-so-smart Miss Know-It-All - Russell, Rachel Renee (New York Aladdin, 2012)
When Miss Know-It-All's inbox overflows with pleas for guidance, Nikki Maxwell, the school newspaper advice columnist, turns to her best friends for help.
750L
103299
Keywords: Advice columns; Newspapers; Middle schools; Schools; Diaries; Humorous stories; Diary fiction; Humorous fiction; Fiction; Juvenile works